Pengaruh Good Corporate Terhadap Manajemen Pajak (Studi Empiris Pada Perusahaan Sub Sektor Perkebunan yang Terdaftar Di BEI Periode 2019-2021) - Yanti, Nur; Haanurat, Ifayani; Razak, Linda Arisanty (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2023)
This study aims to determine the effect of good corporate governance on corporate tax management. Corporte governance is measured by effective tax rate (ETR). This research was conducted using the annual report documentation method of plantation sub-sector copaines listed on teh Indonesia Stock Exchange. The sampling method used this research is puposive sampling. The number of sampels obtained by 15 compaines during the period 2019-2021 compaines. The method of analysis. The results of this study indicate the t test (partial) that teh size of the board on commissioners has no effect on corporate tax management. While indendent commissioners and the compensation of the of the board of commissioners and director have a significant effect on corporate tax management.